Residential Segregation from Generation to Generation: Intergenerational Association in Socio-Spatial Context among Visible Minorities and the Majority Population in Metropolitan Sweden - Björn Anders Gustafsson; Katarina Katz; Torun Österberg (Institute for the Study of Labor (IZA), 2016)
In this paper, we investigate to what degree young adults live in neighbourhoods that are similar, in terms of relative average household income, to the neighbourhoods in which they grew up. We use regression analysis on register data for all individuals who were born in 1974 and lived in metropolitan Sweden in both 1990 and 2006. During this period, the distribution of income in Sweden became far more unequal, unemployment rose dramatically, earlier housing policies were dismantled, the share of "visible minorities" increased dramatically and residential segregation increased very considerably. We find a correlation between average neighbourhood incomes at these two points in the sample's life cycle of 0.44, which is more than three times as high as the household income correlation. We find that half of the children of "visible minorities" grew up in the poorer quartile of neighbourhoods, and of these almost two-thirds remained in the poorest quartile of neighbourhoods as adults. Several measures indicate that intergenerational persistency in context is lower in metropolitan Sweden than was found in a similar study in the United States. However, it appears, that if visible minority individuals lived in a neighbourhood in the lowest part of the distribution in Sweden as a child, the probability that they will do so also as adults is as high as the corresponding probability for a African-American person in the US.
Keywords: J15; J62; R23; 330; Sweden; residential segregation; immigrants; intergenerational persistence